DEVELOPMENT APPLICATIONS Calculating Linear Trend Method of Least Squares of drinking water (PAM) using Macromedia FLASH 5.0 - author author (Jurnal Sistem Informasi, 2005)
In writing this scholarly writer discusses only count Trend Linear least squares method in the use of drinking water (PAM). The objective is that the household can predict the cost of drinking water budget payments for the next months, or 3 months, 6 months, 9 months, and the next year.